Host‐plant dissections reveal contrasting distributions of Crematogaster ants and their symbionts in two myrmecophytic Macaranga species. (24th May 2018) - Houadria, Mickal Y.I.; Klimes, Petr; Fayle, Tom M.; Gullan, Penny J.
Abstract : For the two plant species, for each internode, both contents (ants, coccids, refuse piles) and structure (internode height, numbers of open and occluded ant holes) were recorded. Most coccids were kept in the highest sections of both systems. The fine‐scale distribution showed aggregation of closed holes with ant brood and separation of nematode‐infested refuse piles from eggs. Abstract : 1. Ant–plant mutualisms are among the most widespread and ecologically important insect–plant interactions in the tropics. The multitrophic mutualism involving Macaranga plants (Euphorbiaceae) and Crematogaster ants (Formicidae) is the most diverse in Southeast Asia. This interaction also includes trophobiotic scale insects (Coccidae) and nematodes inhabiting ant refuse piles. 2. Here two myrmecophytic systems were compared, Macaranga trachyphylla with Crematogaster captiosa ( Mt + Cc ) and Macaranga beccariana with Crematogaster decamera ( Mb + Cd ), using a fine‐scale dissection of the stems. For the two plant species, for each internode, both contents (ants, coccids, refuse piles) and structure (internode height, numbers of open and occluded ant holes) were recorded. 3. There were significant patterns in the vertical distribution of ant colonies and their symbionts in the plant stems. Most coccids were kept in the highest sections of both systems, although Mb + Cd hosted a broader range of coccid species than Mt + Cc . Three nematode species were recorded, but with a rather low specificity to plant or ant species. Furthermore, the fine‐scale distribution showed aggregation of closed holes with ant brood and separation of nematode‐infested refuse piles from eggs. 4. The results of this study indicate that ants manipulate spatial colony structure via distribution of brood, holes and the symbionts. It is suggested that ants optimise the location of refuse piles and occluded holes via spatial heterogeneity in their distribution among internodes. This paper discusses the protective role of occluded holes and demonstrates some general interactions with other symbiotic fauna.